Everything you need to know about AIDS - Taylor, Barbara, 1938- (New York : Rosen Pub. Group, 1988)
Discusses the AIDS disease, its discovery, causes, transmission, treatment, and how to protect oneself from contracting the disease.
Includes index.
Bibliography: p. 62.
980
Accelerated Reader AR
Keywords: AIDS (Disease)